First big book of animals - Hughes, Catherine D. (Washington, D.C. : National Geographic, 2010)
Profiles a number of animals from around the world that live in different habitats.
Grassland -- Cheetah -- Zebra -- Giraffe -- Black-and-yellow garden spider -- Lion -- Ocean -- Bottlenose dolphin -- Green sea turtle -- Short-head seahorse -- Sea otter -- Giant Pacific octopus -- Humpback whale -- Blue-striped grunt -- Desert -- Arizona coral snake -- Meerkat -- Desert jerboa -- Thorny lizard -- Camel -- Forest -- Red-eyed tree frog -- Gray wolf -- Black-handed spider monkey -- Blue morpho butterfly -- Koala -- Mountain gorilla -- Raccoon -- North American beaver -- Tiger -- Polar -- Harp seal -- Snowy owl -- Polar bear -- Emperor penguin -- Parent tips -- Animal map.
OSLIS\Gale Nat Geo eBooks(2/2/23).
Includes index.
Outstanding Science Trade Books for Students K-12, 2011
Description based on print version record.
Keywords: Animals -- Juvenile literature; Animals; JUVENILE NONFICTION / Animals / General; Electronic books- OSLIS; Electronic books